Code of Conduct in the South China Sea: More Discord than Accord. (3rd July 2017) - Mishra, Rahul
ABSTRACT: In a departure from its previous stance, China, in August 2017 during the Association of Southeast Asian Nations (ASEAN) Foreign Ministers' meeting, stated that it Beijing was willing to discuss the possibility of re-engaging in a dialogue on the Code of Conduct (CoC) in the South China Sea. The CoC is not a new idea in the region in terms of finding an amicable solution to the South China Sea dispute, which involves China, Taiwan, Vietnam, Brunei, Malaysia, and the Philippines. In 2002, China and the ASEAN member countries officially engaged in formalising the CoC for the first time. However, the CoC finally agreed to was non-binding in nature. While the decision recently taken by the ASEAN countries and China in restarting the negotiations to discuss the CoC again has been seen as a positive move, it is widely believed that, keeping in view China's assertive posture, it is not likely to agree to the CoC anytime soon. This paper discusses the origin and evolution of the CoC in the South China Sea, provides an analysis of China's behaviour with regard to the CoC, and concludes by listing the future prospects for the CoC in the South China Sea.